The handbook of classroom discourse and interaction - Numa Markee (Hoboken, NJ : Wiley Blackwell, 2019)
"The Handbook of Classroom Discourse and Interaction is an authoritative reference work exploring the latest research, methodologies, and theories related to classroom language, teaching, and learning"-- Provided by publisher
Keywords: Classroom environment; LANGUAGE ARTS & DISCIPLINES Linguistics General; Classroom learning centers; Conversation analysis Study and teaching